Effects of 15-deoxy-delta12,14-prostaglandin J2 (15d-PGJ2) and rosiglitazone on human gammadelta2 T cells. - Haishan Li; C David Pauza (PLoS ONE)
Background Thiazolidinediones (TZD) class of drugs, and 15-deoxy-D12,14-prostaglandin J2 (15d-PGJ2) are immune regulators predicted to modulate human autoimmune disease. Their effects on gammadelta T cells, which are involved in animal model and human and animal autoimmune diseases, are unknown. Methodology/principal findings We characterized the activity of rosiglitazone (from the TZD class of drugs) and 15d-PGJ2 in human Vdelta2 T cells. We found that 15d-PGJ2 and rosiglitazone had different effects on Vdelta2 T cell functions. Both 15d-PGJ2 and rosiglitazone suppressed Vdelta2 T cell proliferation in response to IPP and IL2. However, only 15d-PGJ2 suppressed functional responses including cytokine production, degranulation and cytotoxicity against tumor cells. The mechanism for 15d-PGJ2 effects on Vdelta2 T cells acts through inhibiting Erk activation. In contrast, rosiglitazone did not affect Erk activation but the IL2 signaling pathway, which accounts for rosiglitazone suppression of IL2-dependent, Vdelta2 T cell proliferation without affecting TCR-dependent functions. Rosiglitazone and 15d-PGJ2 are designed to be peroxisome proliferator-activated receptor gamma (PPARgamma) ligands and PPARgamma was expressed in Vdelta2 T cell. Surprisingly, when PPARgamma levels were lowered by specific siRNA, 15d-PGJ2 and rosiglitazone were still active, suggesting their target of action induces cellular proteins other than PPARgamma. Conclusions/significance The current findings expand our understanding of how the immune system is regulated by rosiglitazone and 15d-PGJ2 and will be important to evaluate these compounds as therapeutic agents in human autoimmune disease.